The GIANT trial (ECOG-ACRIN EA2186) methods paper: A randomized phase II study of gemcitabine and nab-paclitaxel compared with 5-fluorouracil, leucovorin, and liposomal irinotecan in older patients with treatment-naïve metastatic pancreatic cancer - defining a new treatment option for older vulnerable patients. Issue 3 (April 2023) - Dotan, Efrat; Catalano, Paul; Lenchik, Leon; Boutin, Robert; Yao, Xin; Marques, Helga S.; Ioffe, Dina; Zhen, David B.; Li, Daneng; Wagner, Lynne I.; Simon, Melissa A.; Wong, Terence Z.; et al.
Abstract: Introduction: Pancreatic cancer is the fourth leading cause of cancer-related death in the US with an increasing incidence in older adults (OA) over age 70. There are currently no treatment guidelines for OA with metastatic pancreatic cancer (mPCA) and selecting a chemotherapy regimen for these patients is subjective, based largely on chronologic age and performance status (PS). Geriatric screening tools provide a more objective and accurate evaluation of a patient's overall health but have not yet been validated in patient selection for mPCA treatment. This study aims to elucidate the optimal chemotherapy treatment of vulnerable OA with mPCA and understand the geriatric factors that affect outcomes in this population. Methods/Design: The GIANT (ECOG-ACRIN EA2186) study is multicenter, randomized phase II trial enrolling patients over age 70 with newly diagnosed mPCA. This study utilizes a screening geriatric assessment (GA) which characterizes patients as fit, vulnerable, or frail. Patients with mild abnormalities in functional status and/or cognition, moderate comorbidities, or over age 80 are considered vulnerable. Enrolled patients are randomized to one of two dose-reduced treatment regimens (gemcitabine/nab-paclitaxel every other week, or dose-reduced 5-fluoruracil (5FU)/ liposomal irinotecan (nal-IRI) every other week). GA and quality of life (QoL) evaluations are completed prior to treatment initiation and at each disease evaluation. Overall survival (OS) is the primary endpoint, with secondary endpoints including progression free survival (PFS) and objective response rate (ORR). Enrolled patients will be stratified by age (70–74 vs ≥75) and ECOG PS (0–1 vs 2). Additional endpoints of interest for OA include evaluation of risk factors identified through GA, QoL evaluation, and toxicities of interest for older adults. Correlative studies include assessment of pro-inflammatory biomarkers of aging in the blood (IL-6, CRP) and imaging evaluation of sarcopenia as predictors of treatment tolerance. Discussion: The GIANT study is the first randomized, prospective national trial evaluating vulnerable OA with mPCA aimed at developing a tailored treatment approach for this patient population. This trial has the potential to establish a new way of objectively selecting vulnerable OA with mPCA for modified treatment and to establish a new standard of care in this growing patient population. Trial Registration: This trial is registered with ClinicalTrial.gov Identifier NCT04233866 .